The Challenges of Implementing International Human Rights Norms in Domestic Legal Systems of Developing Countries - Purwanto, Arif; Hassan, Majid (Lembaga Publikasi Ilmiah Nusantara, 2025)
The incorporation of international human rights norms into domestic legal systems of developing countries remains a persistent challenge due to structural, political, and socio-economic constraints. While international human rights treaties establish binding obligations for state parties, their effective implementation often encounters obstacles such as weak legal institutions, lack of political will, limited resources, and cultural or religious tensions that may conflict with universal human rights principles. This article examines the complexities faced by developing countries in harmonizing international human rights standards with national legislation and judicial practices. Through a normative and comparative legal analysis, it identifies the key barriers to implementation, including constitutional limitations, conflicting customary laws, and insufficient enforcement mechanisms. Furthermore, the study highlights best practices from selected jurisdictions that have successfully integrated human rights norms, offering insights into potential pathways for strengthening compliance. The findings underscore the need for a multidimensional approach involving legal reforms, capacity-building of judicial institutions, and enhanced cooperation between international and domestic actors. Ultimately, this article argues that the effective domestication of human rights norms in developing countries is essential to ensure the universality and indivisibility of human rights in the global legal order.